2012
DOI: 10.1371/journal.pone.0033556
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Accumulation of CD14+CD11c+ Dendritic Cells in Gut Mucosa of Celiac Disease after in vivo Gluten Challenge

Abstract: BackgroundOf antigen-presenting cells (APCs) expressing HLA-DQ molecules in the celiac disease (CD) lesion, CD11c+ dendritic cells (DCs) co-expressing the monocyte marker CD14 are increased, whereas other DC subsets (CD1c+ or CD103+) and CD163+CD11c− macrophages are all decreased. It is unclear whether these changes result from chronic inflammation or whether they represent early events in the gluten response. We have addressed this in a model of in vivo gluten challenge.MethodsTreated HLA-DQ2+ CD patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 32 publications
4
47
0
1
Order By: Relevance
“…This is supported by the fact that it has been shown that elevated serum PRL levels in CD patients correlate with disease activity indicated by the presence of malnutrition and the degree of histological damage of the intestinal mucosa [10]. PBMs circulate in blood vessels and migrate to the site of inflammation in the duodenal mucosa [32]; their signaling affects the organism both at the local and the systemic levels. PBMs are known to express PRL and its receptor; the question, however, was whether monocyte-derived PRL plays any role in the pathogenesis of CD.…”
Section: Discussionmentioning
confidence: 93%
“…This is supported by the fact that it has been shown that elevated serum PRL levels in CD patients correlate with disease activity indicated by the presence of malnutrition and the degree of histological damage of the intestinal mucosa [10]. PBMs circulate in blood vessels and migrate to the site of inflammation in the duodenal mucosa [32]; their signaling affects the organism both at the local and the systemic levels. PBMs are known to express PRL and its receptor; the question, however, was whether monocyte-derived PRL plays any role in the pathogenesis of CD.…”
Section: Discussionmentioning
confidence: 93%
“…In CD, neutrophilic influx has been reported previously. 22 Whether IL-21-secreting neutrophils in the celiac lesion have a specific function in B-cell stimulation will need to be investigated. Using serial tissue sections of our pediatric CD patient cohort, we established that the number of IL-17-secreting cells did not increase with disease score and remained comparable with nondiseased control tissues.…”
Section: Discussionmentioning
confidence: 99%
“…tion in animal studies [80][81][82][83][84]. A comparable trend is seen in human 272 diabetes type 1 [85] and CD [86,87] but the effects are controversial in 273 non-celiac gluten sensitivity [88,89]. Most recently, gluten was found 274 to breach tight junction integrity, not only in CD and non-celiac gluten 275 sensitivity, but interestingly enough, also in normal controls [90].…”
mentioning
confidence: 91%